2018
DOI: 10.1037/men0000113
|View full text |Cite
|
Sign up to set email alerts
|

“No messages needed—Just pats on the back”: Exploring young men’s reports of male and female friends’ sexual communications.

Abstract: The current study provided an exploratory mixed methods investigation of the messages undergraduate men received about sex and relationships from their male and female friends. Participants included 310 undergraduate men who provided written responses regarding the specific messages they had received from male and female friends. Descriptive codes included: Just Do It, Meaningful Intimacy, Gentlemen, Postpone Sex, Women's Sexual Desire, and Objectification of Women. Reports of sexual communications were typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Participants noted that part of entry to male spaces and conversations included, at least at times, complicity in verbal expressions of male dominance and disrespect toward women that was troubling. Demonstrating masculinity and male privilege in some male-dominated spaces may require excluding or even demeaning women (Trinh & Choukas-Bradley, 2018). Findings from the present study suggest some trans masculine individuals, concurrent with their acceptance into male-dominated spaces, may lose their sense of connection to their own trans identity or to supportive women’s or queer communities.…”
Section: Discussionmentioning
confidence: 99%
“…Participants noted that part of entry to male spaces and conversations included, at least at times, complicity in verbal expressions of male dominance and disrespect toward women that was troubling. Demonstrating masculinity and male privilege in some male-dominated spaces may require excluding or even demeaning women (Trinh & Choukas-Bradley, 2018). Findings from the present study suggest some trans masculine individuals, concurrent with their acceptance into male-dominated spaces, may lose their sense of connection to their own trans identity or to supportive women’s or queer communities.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional gendered sexual norms are less accepting of women’s active exploration of their sexual desires and pleasures (Hamilton & Armstrong, 2009; Trinh, 2016). Even women themselves follow these norms in evaluating other women (Trinh, 2016; Trinh & Choukas-Bradley, 2018). For instance, Baumeister and Twenge (2002) found that women tended to evaluate other women more harshly for their promiscuity than did men.…”
Section: Perceived Appropriateness and Intentionmentioning
confidence: 99%
“…It may also elicit shame, guilt, depression, anger, and embarrassment (Bry et al, 2017;Bybee et al, 2009;Wagner et al, 2013). In addition, stigmatized sexuality is inhibited, and therefore, the topics discussed are limited (Trinh & Choukas-Bradley, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, people are more prone to talk about sexuality concerns in their romantic relationships when there is trust and safety (Marcantonio et al, 2018). In addition, comfort in an intimate relationship can help people have better sexual communication (Trinh & Choukas-Bradley, 2018). Physical and psychological safety and comfort in the romantic relationship could improve a person's psychological state and help him/her/them combat the discomfort to talk about sexuality (Rubinsky & Hosek, 2020).…”
Section: Introductionmentioning
confidence: 99%